La colmena olvidada: no es el destino inexorable...es la sintonía inefable (2020)
This project is based on an exhaustive investigation on the study of human perception of death, from its biological, psychological and sociological dimension; until finally, focusing on understanding how death is perceived during childhood. Its main purpose is to offer an audiovisual experience of recreation and reflection for children from ages 6 to 8 and their parents, through the production of an animated feature film; which will contribute to educate for death for children. In other words, it is intended to offer a communicational tool with an emotional promise that will allow parents or guardians to introduce and address the concepts of irreversibility and universality of death. The target audience for animated footage are children who are just beginning their school years (6 to 8 years old). The long-term benefit to be achieved is to accelerate the maturation of the concept during childhood...